2010
DOI: 10.1677/erc-10-0136
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging biomarkers in breast cancer: prognosis and prediction

Abstract: Breast cancer treatment has experienced several changes in the past decades due to the discovery of specific prognostic and predictive biomarkers that enable the application of more individualized therapies to different molecular subgroups. These subgroups show specific differences regarding biological clinical behavior. In addition to the classical clinical prognostic factors of breast cancer, established molecular biomarkers such as estrogen receptor and progesterone receptor have played a significant role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
296
1
20

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(338 citation statements)
references
References 129 publications
8
296
1
20
Order By: Relevance
“…However, there are multiple examples of biomarkers being expressed in different, or even the same type, of breast cancer, but which are only of clinical use when expressed above a certain threshold (reviewed in ref. 34). Interestingly, a search on Oncomine showed that eIF4E and eIF5 were not only increased in tumor versus normal breast and lung cancers, but that eIF4E and eIF5 expression was proportionately higher in MBC when genders were compared, substantiating our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are multiple examples of biomarkers being expressed in different, or even the same type, of breast cancer, but which are only of clinical use when expressed above a certain threshold (reviewed in ref. 34). Interestingly, a search on Oncomine showed that eIF4E and eIF5 were not only increased in tumor versus normal breast and lung cancers, but that eIF4E and eIF5 expression was proportionately higher in MBC when genders were compared, substantiating our findings.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The association between Her-2 and Ki-67 in breast cancer patients 5,6,31,34,35 makes Ki-67 an emerging biomarker for breast cancer. 36 This study retrospectively compared 160 cases of Her-2 overexpressing breast cancer patients with 100 cases of Her-2 negative patients in terms of clinicopathological characteristics and the expression of p53 and Ki-67, and further uncovered the connection among Her-2, p53 and Ki-67.…”
Section: Introductionmentioning
confidence: 99%
“…However, treatment decisions extend beyond these traditional parameters. Considerations also include the specific molecular or genetic markers necessary to determine both prognostic (the natural history of the tumor) and predictive (effective therapies) information (Weigel & Dowsett, 2010).…”
Section: Importance Of National Guidelinesmentioning
confidence: 99%